Catalytic co-pyrolysis of woody biomass with waste plastics: Effects of HZSM-5 and pyrolysis temperature on producing high-value pyrolytic products and reducing wax formation. (15th January 2022) - Jin, Xuanjun; Lee, Jae Hoon; Choi, Joon Weon
Abstract: In this study, using an analytical pyrolysis-GC/MS system, pine sawdust was pyrolyzed with polyethylene (PE) and polyethylene terephthalate (PET) in the presence of HZSM-5 to investigate the effect of plastic. Pyrolysis was performed at 500 °C, 600 °C, and 700 °C after 3.0 mg feedstock loading. Chemical compounds were identified and classified into six groups: Monomeric Aromatic Hydrocarbon (MAH), Polycyclic Aromatic Hydrocarbon (PAH), Phenols, Furfurals, Alkenes, and Alkanes. Results showed that pine and PE co-pyrolysis significantly decreased oxygen content from 23.4% (pine only) to 0.3% (pine + PE/HZSM-5), which increased products' HHV from 25.9 MJ/kg to 34.4 MJ/kg. It also revealed that the pine and PE ratio did not heavily influence the petrochemical concentration (aromatic hydrocarbons + alkenes (C ≤ 15) + alkanes (C ≤ 13)). However, a higher plastic ratio led to a higher wax production, which is the reason for poor condensation performance in condenser bio-oil capture. A pinewood sawdust to PE ratio of 3:1 showed the most higher-level petrochemicals and least amount of wax formation. Pine and PET co-pyrolysis produced significantly less wax and similar aromatic hydrocarbons to pine and PE co-pyrolysis. It also made as many acids as PET depolymerization and is a problem for pyrolysis oil use. Highlights: Catalytic co-pyrolysis of pinewood and plastics was studied by analytic pyrolysis. HZSM-5 efficiently reduced the wax production during the pyrolysis of PE. Co-feeding of pinewood with plastic improved the H/C ratio in pyrolytic products. High yield of petrochemicals were obtained at the ratio of 3:1 (pine:PE) at 600 °C.